Partnership or power play? : How Europe should bring development into its trade deals with African, Caribbean and Pacific countries (Oxfam International BostonUS, 2008)
Draws attention to aspects of EPAs that put future economic development at risk. Presents positive policy prescriptions. Uses case studies from the history of the integration of ACP countries into the global economy to draw lessons from both the past and the present.
Keywords: PARTNERSHIP